Bot Fly Types in the Museum of Comparative Zoology (Diptera: Oestridae) - Norman E. Woodley (Psyche: A Journal of Entomology)
The primary types of 5 bot fly taxa in the entomology collection of the Museum of Comparative Zoology are listed and discussed. Syntypes of Gasterophilus pecorum var. zebrae Rodhain and Bequaert and Kirkia minuta Rodhain and Bequaert, previously believed to be lost, are present in the collection. Specimens of two taxa labeled as types have no type status,